The effects of bird's nest as a cryopotective agent on human adipose derived stem cells / Kinarroy Vaithianathan - Kinarroy, Vaithianathan. (2014)
One of the most popular concepts currently is the use of stem cells in the regenerative therapy which replaces the lost or dysfunctional part in a human body. In order for a patient to benefit from such therapies, the stem cell source should be always made available. Therefore, it is important to preserve these cells so that they are always available for treatments. Cryopreservation is one of the important methods to preserve cells and tissues where it can be used for the recovery of damaged tissues and organs. Cryopreservation of stem cells is mainly to minimize any form of damage to biological materials at very low temperatures while freezing and also during storage. This issue can be addressed with the addition of a cryoprotective agent. Dimethyl sulfoxide (DMSO) is a common cryoprotective agent which is a polar compound originally created for the use as a solvent. However the use of DMSO may result in the toxicity of cells. The bird’s nest or also known as edible bird’s nest (EBN) is a health food with many traditional medicinal properties. Therefore, the objectives of this study are to evaluate the efficiency of EBN to act as a cryoprotective agent, to evaluate the differentiation ability to express the following lineages; osteogenic, adipogenic and chondrogenic after cryopreservation with the respective cryoprotectants (10% DMSO+90% FBS, 5% DMSO+1% EBN+94% FBS and 1% EBN+99% FBS) and to evaluate the proliferative rate of the cryopreserved human adipose derived stem cells with the respective cryoprotectants (10% DMSO+90% FBS, 5% DMSO+1% EBN+94% FBS and 1% EBN+99% FBS). This study is designed to evaluate the ability of EBN to either act as a cryoprotectant to substitute DMSO or to act as a supplement to DMSO. The human adipose tissue were collected from the PPUM was isolated and cultured up to second passage. Then, the cells were cryopreserved in the respective cryoprotectant; 10% DMSO+90% FBS (Control), 5% DMSO+1% EBN+94% FBS and 1% EBN+99% FBS for a month. After a month, the cells were thawed and cultured for the following tests; cell viability test, resazurin test and differentiation into three lineages (adipogenic, chondrogenic and osteogenic). Then, the differentiated lineages were stained and the respective surface areas were determined. It can be concluded that the human adipose derived stem cells preserved in 10% DMSO+99%FBS had exhibited a higher result as compared to cells preserved in 5% DMSO+1% EBN+94%FBS and 1% EBN+99% FBS. Hence making DMSO still a good and superior cryoprotective agent. DMSO on its own can support the growth of the cells which can be seen in 10% DMSO+99% FBS and does not require the presence of EBN. Therefore, it can be concluded that EBN cannot act as a cryoprotective agent. EBN is better to be used in in vitro cell culture experiments instead of it as a cryoprotective agent.